Mental health of Syrian refugee adolescents: how far have we come? - Sinem Akgül; Şenel Hüsnü; Orhan Derman; Elif Özmert; Aysun Bideci; Enver Hasanoğlu (The Turkish Journal of Pediatrics)
Among the consequences of war, its impact on the mental health of children and adolescents is one of the most significant. A previous study from our team evaluated the psychiatric symptoms of Syrian refugee adolescents living in one of Turkey`s Temporary Accommodation Centers (TACs) in 2016. Findings suggested that mental health had been compromised in these teens. Since then many measures have been taken to address this problem. The aim of the current study was to re-assess the mental health status of adolescents living in the same center. A total of 76 adolescents (35 female, 41 male) aged between 12-18 years (14.2 ± 0.83 years) received the Brief Symptom Inventory (BSI) which assessed their anxiety, depression, negative self-concept, somatization and hostility levels in addition to a Global Severity Index (GSI). Results > 1.0 indicated psychopathological symptoms. All BSI sub-scores decreased from 2016 to 2019 showing significant improvement in psychopathological symptoms. The most significant change was in the GSI score which decreased from 2.15 to 0.8. For the 2019 participants a significant correlation was found between years of stay at the camp and the depression subscale. Evaluation to assess gender differences found that adolescent girls reported significantly higher scores than males in anxiety, depression, somatization and the global severity index. This study has shown that interventions designed to tackle post-traumatic stress symptomology may have been effective in improving the mental health status of these teens and can provide a roadmap for tackling existing issues in vulnerable conditions. Additionally, females are under higher risk for psychopathology so gender targeted interventions may specifically be necessary to deal with such issues.